Sex differences in the relationship between cognitive impairment and overweight or obesity in late life: A 3-year prospective study. Issue 9 (March 2019) - Noh, Hye-Mi; Han, Junhee; Kim, Yeo Jin; Jung, Jin-Hyung; Roh, Yong Kyun; Song, Hong Ji
Abstract : Abstract: The relationship between body weight changes in late life and cognitive function is controversial. We investigated whether weight gain or loss in late life affected cognitive function in community-dwelling older adults over a 3-year period. Our study used data from the Survey of Living Conditions and Welfare Needs of Korean Older Persons and included 3859 subjects (aged ≥65 years) with normal cognition at baseline. At baseline and the 3-year follow-up, body weight and height were measured, and cognitive function was assessed using the mini-mental state examination. Based on their body mass index (BMI) at baseline and follow-up, we divided the subjects into 4 groups: weight gain (baseline BMI <23 kg/m 2 and follow-up BMI ≥23 kg/m 2 ); weight loss (baseline BMI ≥23 kg/m 2 and follow-up BMI <23 kg/m 2 ); stable overweight/obese (BMI ≥23 kg/m 2 at both visits); and stable non-overweight/obese (BMI <23 kg/m 2 at both visits). Incidence rates (IRs) of cognitive impairment per 100 persons and IR ratios (IRRs) were calculated for each group and adjusted for confounding variables. At the 3-year follow-up, 610 cases of cognitive impairment (15.8%) were identified. The stable overweight/obese group had the lowest IR (14.0, 95% confidence interval [CI] 12.45–15.71) and was therefore used as the reference group when calculating IRRs for cognitive impairment. When men and women were evaluated separately, IRs between groups were significantly different only for women. The stable non-overweight/obese group (IRR 1.65, 95% CI 1.22–2.22) and the weight gain group (IRR 1.93, 95% CI 1.24–3.01) had higher IRs than those in the stable overweight/obese group. As a gain or loss of adiposity, the IR of the weight gain group (IRR 1.17, 95% CI 0.74–1.84) was not different from that of the stable non-overweight/obese group. Also, the IR of weight loss group (IRR 1.09, 95% CI 0.71–1.67) was not significantly different from that of the stable overweight/obese group. We suggest that overweight or obese older women at baseline had cognitive benefits. However, additional gain or loss of adiposity in late life did not affect the risk of cognitive impairment. Abstract : Supplemental Digital Content is available in the text